PERANCANGAN DAN PENGEMBANGAN PRODUK ALAT TERAPI JARI UNTUK MEMBANTU PROSES REHABILITASI PASIEN PASCA STROKE - Rizal Mustofa; Rifky Ismail; Budi Setiyana (JURNAL TEKNIK MESIN, 2022)
Stroke is one of the leading causes of death in the world caused by blockage and broken blood vessels. To restore its function back, a rehabilitation process is needed, one of which is using finger therapy tools. The purpose of this study was to determine the structural strength of the finger therapy device, both on the support structure of the arm and on the structure of the palm of the hand. This study uses the software to determine the acceptable structural strength of the finger therapy device. Based on the simulations that have been carried out, the results obtained are the maximum stress of 0.087 MPa on the forearm support structure and 45,798 MPa on the palm support structure. The total deformation value is 0.001 mm in the forearm support structure and 1.2 mm in the palm support structure. While the safety factor value obtained is 15 on the forearm support structure and 1.18 on the palm support structure. From these results the structure is declared safe and can withstand the maximum load.